No association between the functional cannabinoid receptor type 2Q63R variants and inflammatory bowel disease in Turkish subjects - (:unkn) unknown (My University, 2014)
0

Background/Aims: The endocannabinoid system can exert beneficial effects on gastrointestinal inflammation, and cannabinoid receptor-2 (CB2) agonists may represent a new therapeutic approach in inflammatory bowel disease (IBD). A functional CB2 Q63R polymorphism (rs35761398) in the CNR2 gene has been shown to affect the immunomodulating properties of the CB2 receptor. We sought to investigate whether the functional CB2 Q63R polymorphism (rs35761398) is associated with IBD susceptibility in a Turkish clinical sample. Materials and Methods: A total of 202 IBD patients, comprising 101 Crohn's disease (CD) patients and 101 ulcerative colitis (UC) patients, and 101 healthy controls were included in the study. The CB2 Q63R polymorphism was genotyped using real-time PCR. Results: There were no significant differences in the genotype frequencies of the three study groups. The odds ratio of the minor Q allele for CD relative to the common R allele was not significant (OR =1.02, 95% CI =0.67-1.56, p=0.99). Similarly, the odds ratio of the minor Q allele for UC relative to the common R allele did not reach statistical significance (OR =1.10, 95% CI =0.72-1.68, p=0.75). Moreover, the genotype frequencies did not show any significant association with the disease extent in either CD (p= 0.71) or UC patients (p=0.59). Conclusion: These pilot findings suggest that CB2 Q63R polymorphism does not play a major role in genetic susceptibility to IBD or in its disease phenotypes among Turkish subjects.
Keywords: Cerrahi